A comparative study of the formation and development of the establishment of government centers in the cities on the edge of the desert from the beginning until now and the feasibility of developing a strategic model for the establishment of government centers in these cities - Mohammad Ali Jamalizadeh; Abbas Masoudi (تحقیقات کاربردی علوم جغرافیایی, 2025)
Ancient cities have always possessed inherent distinctions from contemporary cities, which are evident in their physical structures and overall layouts, allowing them to be easily differentiated from their modern counterparts. These distinctions, influenced by economic, political, cultural, and social conditions, have resulted in varying degrees of change in the urban structure and have given rise to two types of urban growth. Organic growth is characterized by a continuous and coherent expansion that prioritizes form in relation to function, in stark contrast to the fragmented and discrete nature of global cities in the modern era. This study seeks to address whether it is feasible to apply the characteristics and developmental patterns of ancient cities in today's world by examining the evolution of urban form throughout history up to the present day. Alternatively, can a favorable outcome be achieved by integrating certain characteristics of ancient cities into contemporary urban environments? Based on this objective, the study explores the evolution of urban form across three historical periods - pre-Islamic, post-Islamic, and the modern era - with a particular focus on the establishment of governmental centers in the central desert of Iran. The comparative method of induction is employed to discuss the subject matter in line with the research assumptions. The findings indicate that the first and second hypotheses have yielded more significant results in a greater number of unsuccessful experiments. Conversely, the third hypothesis has been more successful in a wider range of experiments with diverse outcomes. Moreover, considering the success rate of 0.100 and the absence of unsuccessful experiences for the Kerman experiment, it can be argued that this hypothesis is relatively superior and preferable for assessing the success rate of related projects.